Turismo comunitario y planificación turística del espacio rural en la comunidad Chimborazo, Parroquia San juan, Cantón Riobamba - Cáceres Guzmán, Daniel Alexander (2025)
The research aimed to develop tourism planning focused on community tourism in rural areas in the Chimborazo Community, San Juan Parish, Riobamba Canton, Chimborazo Province. The problem lies in the fact that the inhabitants of the San Juan Parish do not actively participate in tourism management and the use of resources, which has limited their economic growth, so it is necessary to implement tourism planning that integrates residents and promotes the conservation of the natural environment; giving way to the following formulation of the problem: How does tourism planning affect community tourism in rural areas in the community of Chimborazo, specifically in the parish of San Juan, Riobamba canton, Chimborazo Province? The methodology applied was a non-experimental, field, mixed design, inductive, and analytical. Two surveys were applied to collect information: one to five tourism managers in San Juan and another to 381 tourists. The results showed limited participation of residents in tourist activities. In addition, there are deficiencies in the accommodation structures. Likewise, tourists fail to learn about ancestral customs, traditions, or rituals, which has generated a disconnect between tourism, community well-being, and tourist satisfaction. When testing the hypothesis, it was found that with a coefficient of 0.846, they show a strong positive correlation. In conclusion, the design of tourism planning focused on community tourism will become a key tool that will contribute to the economic, social, and cultural development of the community of San Juan.